2018
DOI: 10.31101/jhtam.441
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between age of first dating and sexual behavior of adolescents and young adults in indonesia

Abstract: Premarital sexual behavior among Indonesian adolescents currently becomes easier to be found than previous generation. Based on health survey in 2017, both female and male adolescents admitted that they experienced dating since the aged of 16. Data showed that adolescents who were in relationship admitted having premarital sex than the common adolescents. This study’s objectives was to investigate the correlation between age of first dating and sexual behavior among adolescents and adults in Indonesia. The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 5 publications
1
7
0
7
Order By: Relevance
“…Mostly the informants in her study also mentioned if they were coming into the same pattern sexual activity as in this study, include holding hands, hugging, kissing, wet kissing, necking, petting, oral sex, moderate petting, heavy petting, making love and then intercourse (Kisriyati, 2013). This result also supported by others study conducted by (Sari & Rokhanawati, 2018), as they found if dating with boyfriend has correlation on their sexual behavior (Sari & Rokhanawati, 2018). Peer also contribute to the pre-marital pregnancy as reveal by a study conducted in Indonesia (Astuti et al, 2020).…”
Section: Boyfriend or Peersupporting
confidence: 81%
“…Mostly the informants in her study also mentioned if they were coming into the same pattern sexual activity as in this study, include holding hands, hugging, kissing, wet kissing, necking, petting, oral sex, moderate petting, heavy petting, making love and then intercourse (Kisriyati, 2013). This result also supported by others study conducted by (Sari & Rokhanawati, 2018), as they found if dating with boyfriend has correlation on their sexual behavior (Sari & Rokhanawati, 2018). Peer also contribute to the pre-marital pregnancy as reveal by a study conducted in Indonesia (Astuti et al, 2020).…”
Section: Boyfriend or Peersupporting
confidence: 81%
“…Lack of access to information related to reproductive health has an unwanted impact on the situation (Astuti, Hirst, et al, 2020). This results in adolescents tend to be more often and earlier involved in sexual practices than adolescents who have parents with higher education (Sari & Rokhanawati, 2018).…”
Section: Factors Influencing Communication Of Sexual and Reproductive Healthmentioning
confidence: 99%
“…Forty percent of teenagers are pregnant before 20, and 30% of these pregnancies end in abortion (Heart, 2010). Meanwhile, 7.7% in 2012 and 9% Indonesian high school students engaged in sexual intercourse (Bauer, 2015;Sari & Rokhanawati, 2018).…”
Section: Introductionmentioning
confidence: 99%